Life Evaluation of High-speed EMU Variable Gauge Bogie Axle Box Bearing under Partial Load - Zhiwei ZHENG; Zhihui HUANG (机车电传动)
The life of the axle box bearing of a high-speed EMU variable gauge bogie was evaluated. The axle box bearing should take two kinds of gauge and bear partial load due to the influence of the wheel track distance, thus producing the partial load effect and the edge effect, which made the line contact load bearing end failure earlier than the other parts. Therefore, it was necessary to evaluate the expansion life of the axle box bearing of the variable gauge bogie. The fatigue life of the double row cylindrical roller bearing was calculated and the roller of the double row cylindrical roller bearing was repaired. The fitting curve between the different load and the fatigue life of the roller bearing was obtained by numerical analysis. The calculation showed that the partial load greatly affected the fatigue life of the bearing, but it could still meet the design requirements.